An Non Destructive Test for the Detection of Weld Defects Using Image Processing - Kalaiselvi V; John Aravindhar D (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Welding is a fabrication of joining materials into one component. Defects are unavoidable during the welding process, and hence the inspection of welds is a most important task in many industries. In this work, a Computer Aided Detection (CAD) system is designed to detect weld defects based on image processing techniques. It is a non-destructive testing which uses X-ray images. The proposed system mainly consists of three stages; gradient image formation, filtration by Gaussian pyramidal filters algorithm and segmentation by Expectation and Maximization (EM) algorithm. In this study, GD X-ray weld image database is used to evaluate the proposed system. The performance analysis of the proposed system is done by measuring the sensitivity, specificity, and accuracy of the segmented image with the help of its corresponding ground truth images.